Retracted:Assessment of the low-field magnetic resonance imaging for the brain scan imaging of the infant hydrocephalus: The article was retracted after a thorough investigation due to infringement of copyrights, plagiarism and violations of IJHS ethical guidelines - Rizvi, Qaim Mehdi; Singh, Sarika (International Journal of Health Sciences, 2023)
In adherence with IJHS commitment to uphold the highest standards of scholarly integrity and transparency and in compliance with the Committee on Publication Ethics (COPE) guidelines. The article “Assessment of the low-field magnetic resonance imaging for the brain scan imaging of the infant hydrocephalus’ was retracted after thorough investigations that confirmed that the article included several plagiarised images without the consent of the original authors (1,2). Upon receiving a notification from the authors of the (1), an investigation was launched and the authors were invited to respond. We reached the conclusion that the article has violated the ethical policy of the journal beyond any doubt and at least five of the existing images in the article are copied from (1) and another image is copied from (2). The authors of the article were informed by the decision. References 1. Harper JR, Cherukuri V, O’Reilly T, Yu M, Mbabazi-Kabachelor E, Mulando R, et al. Assessing the utility of low resolution brain imaging: treatment of infant hydrocephalus. Neuroimage Clin. 2021 Nov 23;32:102896. 2. Cohen AR. Brain Tumors in Children. N Engl J Med. 2022 May 19;386(20):1922–31.